Mycobacterium Tuberculosis Genotype Variation and Household Transmissibility in Different Tuberculosis Epidemic Areas of Guangxi, China - Zhezhe Cui (Prince of Songkla University, 2024)
Doctor of Philosophy ( Epidemiology (International Program)), 2019